Effect of Acute Limb Ischemia on the Mortality of Patients with Extracorporeal Membrane Oxygenation Established by Femoral Vein-Arterial Catheterization and Analysis of Related Risk Factors. (31st August 2021) - Li, Xiang; Chen, Guang; Zhang, Sheng; Zheng, Xinting; Zhao, Wenjun; Hong, Dun
Abstract : Extracorporeal membrane oxygenation (ECMO) is a common treatment for cardiopulmonary failure. Although it can effectively reduce the mortality of patients with cardiopulmonary failure, it still has a high mortality rate, such as acute limb ischemia (ALI), stroke, liver and kidney failure, and other related complications and related causes of death. This study aims to explore the impact of ALI on the mortality of VA-ECMO patients in hospital and 6 months after discharge and analyze the occurrence of ALI and related factors that affect the mortality of VA-ECMO in hospital and 6 months after discharge. The results showed that the smoking history was an independent risk factor for ALI, and age, diabetes, cardiac arrest, first time of ECMO, and hyperbilirubinemia were associated risk factors for in-hospital mortality. Cardiac arrest and ALI were associated risk factors for mortality at 6 months after discharge. Although ALI is not significantly associated with VA-ECMO in-hospital mortality, it is a risk factor for mortality at 6 months after discharge, and medical personnel should therefore strive to reduce and avoid ALI.